2022
DOI: 10.3390/su14021040
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Presence Volatile Organic Compounds (BTEX) in the Ambient Air and Biogases Produced by a Shiraz Landfill in Southern Iran

Abstract: The generation and emission of volatile organic compounds (VOCs) affects the environment and air quality, playing an important role in global warming, depletion of atmospheric ozone and emission of unpleasant odors, but also directly affect human health. This study investigated the health risks of benzene, toluene, ethylbenzene, xylene (BTEX) compounds and biogas released in and around the municipal landfill. Sampling of the VOCs was carried out by the 1501NIOSH method from 8 points over 5 months. The samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…As shown in Exhibit 5, there were positive correlations between CH 4 , NH 3 , H 2 S, and VOCs with relative humidity, and the strength of the relationship was not decisive. However, a previous study reported a direct impact on the emission of VOCs, and higher levels of VOCs were noted at high relative humidity (Khademi et al., 2022).…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Exhibit 5, there were positive correlations between CH 4 , NH 3 , H 2 S, and VOCs with relative humidity, and the strength of the relationship was not decisive. However, a previous study reported a direct impact on the emission of VOCs, and higher levels of VOCs were noted at high relative humidity (Khademi et al., 2022).…”
Section: Resultsmentioning
confidence: 93%
“…In cities, ozone formation and destruction are complex mechanisms and depend on solar radiation and pollutants emissions from traffic. According to other studies, the ozone concentrations at the ground level are strongly related to seasonal, episodic, and diurnal fluctuations [73][74][75][76][77][78][79][80]. In areas with high levels of vegetation and abundant sunlight, such as forests or densely vegetated regions, VOC emissions from plants can contribute to ozone formation.…”
Section: Discussionmentioning
confidence: 98%
“…Los gases de efecto invernadero tales como CO2, CH4, N2O y gases fluorados son el resultado de la actividad humana, como la generación de electricidad y producción de calor (25%), agricultura, silvicultura y otros usos de la tierra (24%), industria (21%), transporte (14%), edificios (6%) y otras energías (10%), (Cinar et al, 2022). Los vertederos públicos representan la forma más sencilla de gestionar los residuos ya que son de bajo costo y no requieren de un personal altamente calificado, sin embargo, tienen un gran impacto negativo debido a la producción de gases de vertedero, como CH4, CO2 y más de 200 gases distintos (causados por descomposición de la materia orgánica en condiciones anaeróbicas) que tienen un gran impacto en la contaminación atmosférica, y además representan un riesgos para la salud humana (Khademi et al, 2022). Además, estas emisiones son una amenaza en el agotamiento de la capa de ozono, cambio climático, acidificación, eutrofización y ecotoxicidad del ambiente.…”
Section: Discussionunclassified